Predictors of Spiritual Well-being in the Episcopal Church during the COVID-19 Pandemic - Village, Andrew (Journal of Anglican studies, 2025)
The COVID-19 pandemic seems to have caused both declines in psychological well-being and increases in spirituality and religious coping. This paper explores the relationships of spiritual and psychological well-being in a sample of 3,403 Anglicans from the Episcopal Church (USA) who completed an online survey in 2021 during the COVID-19 pandemic. Spiritual well-being improved more among women than among men, among older than younger people, among Black or African Americans than among other ethnicities, among those who lived alone and among clergy than among lay people. Positive change in spiritual well-being was also associated with psychological type preferences for extraversion, intuition and feeling. Emotional volatility was associated with more negative changes in spiritual well-being. Multiple regression suggested that spiritual well-being was more closely associated with positive, rather than negative, psychological affect.